Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am trying to show an integral transform has a fixed point.

Let $H \in (0,1)$ and consider the following integral transform whose kernel is the density of fractional Brownian motion: $$T_H f(x) = 2 \int_{0}^{\infty} \frac{1}{\sqrt{2 \pi y^{2H}}}\exp\left(\frac{-x^2}{2y^{2H}}\right) f(y) dy.$$

I want to show $T_H$ has a fixed point given by $ \phi(x) = \exp(-c|x|^{\frac{1}{2(1-H)}})$ for some $c \in \mathbb{R}$. That is $T_H \phi (x) = \phi (x)$. Although I do not know if this is true in general I know it is true for the case $H=\frac{1}{2}$.

1) What is the Fourier transform of $T_H \phi(x)$ with respect x? Is it equal to a multiple of the Fourier transform of $\phi(x)$?

The motivation for the problem is is that we know for the $H=\frac{1}{2}$ and $c=2$ then $\phi(x) = e^{-2|x|}$ is a fixed point for $T_{\frac{1}{2}}$. That is the Fourier transform of $T_{\frac{1}{2}}e^{-2|x|} = 2 \int_{0}^{\infty} \frac{e^{\frac{-x^2}{2y}}}{\sqrt{2 \pi y}} e^{-2y} dy$ is equal to $\frac{4}{k^2+4}$ which is the same as the Fourier transform of $e^{-2|x|}$. This is from a paper titled iterated random walk by L. Turban if anyone is interested in the reference.

share|cite|improve this question
up vote 4 down vote accepted

It is rather easy to verify numerically, that $\phi(x) = \exp(-c \vert x \vert^{\frac{1}{2(1-H)}} )$ does not satisfy $T_H \phi = \phi$.

To this end it is enough to observe that $(T_H \phi_c)(x) = c^{-2 (1-h)^2} (T_H \phi_1)(x c^{2 h(1-h)})$, which is obtained via changing variables $y \to c^{-2(1-h)} y$. This scaling tells you that if $T_H \phi_c = \phi_c$, then $T_H \phi_1 = c^{-2(1-h)^2} \phi_1( x c^{2 h (1-h)} )$.

Thus it suffices to show that functional forms of $T_H \phi$ and $\phi$ are different for your purported function. So we set $c=1$ and change variables into $y \to t^{2(1-h)}$. This gives

$$ (T_H \phi)(x) = 2(1-h) \sqrt{\frac{2}{\pi}} \int_0^\infty t^{2(1-h)^2} \mathrm{e}^{-t} \exp(-\frac{x^2}{2} t^{-4 h (1-h)} ) \frac{\mathrm{d} t}{t} $$ The integral can be evaluate in terms of Fox H-function. Specifically, in terms of Mellin-Barnes integral:

$$ (T_H \phi)(x) =\sqrt{\frac{2}{\pi}} \frac{z^{2 \rho_h}}{2h} \frac{1}{2 \pi i} \int_{\gamma - i \infty}^{\gamma+i \infty} \left( \Gamma(s) \Gamma( -\rho_h + \frac{s}{\kappa_h} ) z^{-\frac{2s}{\kappa_h }} \right)\mathrm{d}s $$ where $\gamma$ is an arbitrary $\gamma > \rho_h \kappa_h$ and $z = \frac{x}{\sqrt{2}}$ and we introduced $\kappa_h = 4 h(1-h)$ and $\rho_h = \frac{1-h}{2 h}$.

The Mellin-Barnes integral can be evaluated as the sum over poles of $\Gamma$ functions at $s= -k$ for $k \in \mathbb{Z}^+$ and at $s = \rho_h \kappa_h - k \, \kappa_h$, giving $$ \begin{eqnarray} (T_H \phi)(x) = \frac{z^{2 \rho_h} }{2 h} \sqrt{\frac{2}{\pi}} && \sum_{k=0}^\infty (- z^{\frac{2}{\kappa_h}} )^k \frac{\Gamma(-\rho_h - \kappa_h \, k )}{k!} + \\ \sqrt{\frac{4 \rho_h \kappa_h}{\pi}} && \sum_{k=0}^\infty (- z^{ 2 } )^k \frac{\Gamma(\rho_h \kappa_h - k \, \kappa_h )}{k!} \end{eqnarray} $$

When $h = \frac{1}{2}$, $\kappa_{1/2} = 1$ and $\rho_{1/2} = \frac{1}{2}$. Then the sums evaluate exactly:

$$ \begin{eqnarray} T_{1/2} \phi &=& \frac{x}{\sqrt{2}} \sqrt{ \frac{2}{\pi} } \sum_{k=0}^\infty (-\frac{x^2}{2})^k \frac{\Gamma(-\frac{1}{2}-k)}{k!} + \sqrt{ \frac{2}{\pi} } \sum_{k=0}^\infty (-\frac{x^2}{2})^k \frac{\Gamma(1/2-k)}{k!} \\ &=& -\sqrt{2} \sinh( \sqrt{2} x) + \sqrt{2} \cosh( \sqrt{2} x) = \sqrt{2} \, \exp( -\sqrt{2} x) \end{eqnarray} $$

It is also possible to evaluate these sums for rational values of $h$, but expressions involve hypergeometric functions and stop being so simple.

Added: Below we construct the $T_H \psi$, where $\psi(x)$ is a general Fox H-function. The class of Fox H-functions is a natural place to search for solutions of $T_H \psi = \psi$ because operator $T_H$ maps a Fox H-function into another Fox H-function. Specifically, let

$$ \begin{eqnarray} \psi(x) &=& H^{m,n}_{p,q}\left( \left. \begin{array}{c} (a_1, \alpha_1), \ldots, (a_p, \alpha_p) \\ (b_1, \beta_1), \ldots, (b_q, \beta_q) \end{array} \right\vert x\right) \\ &=& \frac{1}{2 \pi i} \int_{\gamma-i \infty}^{\gamma + i \infty} \frac{ \prod_{k=1}^m \Gamma(1-a_k - \alpha_k s) \prod_{k=1}^n \Gamma(b_k + \beta_k s) }{ \prod_{k=m+1}^p \Gamma(1-a_k - \alpha_k s) \prod_{k=n+1}^q \Gamma(b_k + \beta_k s) } x^{-s} \mathrm{d} s \end{eqnarray} $$


$$ (T_H \psi)(x) = \frac{1}{\sqrt{2 \pi}} \frac{1}{h} \left( \frac{x^2}{2} \right)^{\frac{(1-h)}{2h} } H^{m,n+1}_{p,q+1}\left( \left. \begin{array}{c} (a_1, \alpha_1), \ldots, (a_p, \alpha_p) \\ \left( -\frac{1-h}{2h}, \frac{1}{2h}\right), (b_1, \beta_1), \ldots, (b_q, \beta_q) \end{array} \right\vert \left(\frac{x^2}{2}\right)^{\frac{1}{2h}} \right) $$

Now let's understand the mechanics of how it works for $h=\frac{1}{2}$. Your function $\phi(x)$ with $h=\frac{1}{2}$ is $\exp(-x) = H^{0,1}_{0,1}(x)$ with $\beta_1=1$ and $b_1 = 0$, so

$$ \begin{eqnarray} \left. (T_H \phi)(x) \right\vert_{h=\frac{1}{2}} &=& \frac{2}{\sqrt{2 \pi}} \left( \frac{x^2}{2} \right)^{\frac{1}{2} } H^{0,2}_{0,2}\left( \left. \begin{array}{c} - \\ \left( -\frac{1}{2}, 1\right), (0, 1) \end{array} \right\vert \frac{x^2}{2} \right) \\ &=& \sqrt{\frac{2}{\pi}} \left( \frac{x^2}{2} \right)^{\frac{1}{2} } \frac{1}{2 \pi i} \int_{\gamma-i \infty}^{\gamma+i \infty} \Gamma\left( -\frac{1}{2} + s\right)\Gamma(s) \left( \frac{x^2}{2} \right)^{-s} \mathrm{d} s \\ &=& \sqrt{\frac{2}{\pi}} \left( \frac{x^2}{2} \right)^{\frac{1}{2} } \frac{1}{2 \pi i} \int_{\gamma-i \infty}^{\gamma+i \infty} \sqrt{\pi} \Gamma(2s-1) 4^{1-s} \left( \frac{x^2}{2} \right)^{-s} \mathrm{d} s \left. = \right|_{s \to \frac{s}{2}} \\ &=& 2 x \frac{1}{2 \pi i} \int_{\gamma-i \infty}^{\gamma+i \infty} \Gamma(s-1) \left( \sqrt{2} x \right)^{-s} \mathrm{d} s \\ &=& (2 x) \left( \frac{\exp(- \sqrt{2} x)}{\sqrt{2} x} \right) = \sqrt{2} \exp(- \sqrt{2} x) \end{eqnarray} $$

Notice that the use of tuplication identity for $\Gamma(x)$ was essential here, this essentially proves that within the family of Fox H-functions the solution to $(T_H \psi)(x) = c_1 \psi(c_2 x)$ for some constants $c_1$ and $c_2$ is only possible for $h=\frac{1}{2}$.

Now, the family of Fox H-functions is big and encompasses all hyper-geometric elementary functions, i.e. those that satisfy a linear differential equations with coefficients polynomial in $x$.

If you would like to find the eigenfunction of $T_h$ operator, I would suggest playing with quadrature rules. Suppose $(T_H f)(x) = \sum_{i=1}^n \omega_i K(x, y_i) f(y_i)$. Solve the system of equations

$$ \sum_{i=1}^n \omega_i K(x_j, y_i) f(y_i) = f(x_j) $$ numerically, which would allow you to explore the eigen-function for $h \not= \frac{1}{2}$.

share|cite|improve this answer
@user7980 Sorry for the confusion. Symbol $\simeq$ was meant to be the equality. Details are not important, I was making a point that if you could see that $T_H \phi_1(x)$ and $\phi_1(x)$ have different functional forms, then there does not exist such $c$ that $\phi_c(x)$ satisfies $T_H \phi_c(x) = \phi_c(x)$. – Sasha Aug 31 '11 at 19:25
In regards to your question about possible relaxation for the ansatz for $\phi(x)$ as polynomial types the exponential. This is unlikely, from what I can tell. Result of evaluation of $T_H \phi$ would again be Fox H type, reducing to exponential only for single value of $h$. – Sasha Aug 31 '11 at 19:28
@robjohn I should have really said $(T_H \phi_c)(x) = c^{-2 (1-h)^2} (T_H \phi_1)(x c^{2 h(1-h)})$. I will edit the post with this correction. – Sasha Aug 31 '11 at 21:44
Good work (+1). If I had had some more free time this morning, I was going to look into finding the fixed point of $T_H$, but you got it first. – robjohn Aug 31 '11 at 23:18
@user7980 I am afraid the answer is in negative. See the addition to my answer above the horizontal line delimiter marked with Added. – Sasha Sep 1 '11 at 15:33

As in your other problem, I will assume that the Fourier Transform is normalized as $$ \hat{f}(t)=\int_{-\infty}^\infty f(x)\;e^{-ixt}\;\mathrm{d}x $$ As shown in my answer to that question, $$ \int_{-\infty}^\infty e^{\frac{-x^2}{2y^{2H}}}e^{-ixt}dx=\sqrt{2\pi y^{2H}}\;e^{-y^{2H}/2\;t^2} $$ By linearity, the Fourier Transform of $T_Hf(x)$ is $$ \begin{align} &\mathcal{FT}\;\;2\int_{0}^{\infty} \frac{1}{\sqrt{2 \pi y^{2H}}}\exp\left(\frac{-x^2}{2y^{2H}}\right) f(y) dy\\ &=2\int_{0}^{\infty}\frac{1}{\sqrt{2 \pi y^{2H}}}\sqrt{2\pi y^{2H}}\;\exp(\frac{-y^{2H}}{2}t^2)f(y)\;dy\\ &=2\int_{0}^{\infty}\;\exp(\frac{-y^{2H}}{2}t^2)f(y)\;dy \end{align} $$ Plugging in $f(y)=\phi(y)=\exp(-cy^{\frac{1}{2(1-H)}})$, we get $$ \begin{align} &\mathcal{FT}\;\;T_H\phi(t)\\ &=2\int_{0}^{\infty}\;\exp(\frac{-y^{2H}}{2}t^2)\exp(-cy^{\frac{1}{2(1-H)}})\;dy \end{align} $$ I don't see a way of continuing unless $H=\frac{1}{2}$, in which case, $$ \begin{align} &\mathcal{FT}\;\;T_{\frac{1}{2}}\phi(t)\\ &=2\int_{0}^{\infty}\;\exp(\frac{-y}{2}t^2)\exp(-cy)\;dy\\ &=\frac{4}{2c+t^2} \end{align} $$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.